Decolonizing Science Diplomacy: A Case Study of the Dominican Republic’s COVID-19 Response - Mencía-Ripley, Aída; Paulino-Ramírez, Robert; Jiménez, Juan Ariel; Camilo, Odile (Frontiers in Research Metrics and Analytics, 2021)
The COVID-19 pandemic forced healthcare systems globally to handle a dramatic surge in healthcare utilization while also taxing available testing resources. In the context of healthcare systems in Latin America and the Caribbean, COVID-19 added to the existing burden of infectious diseases related to endemic infections such as arboviruses and HIV. In the Dominican Republic, testing is supplied mostly by the private sector and a national public laboratory. The surge in testing demands laid bare a lack of installed capacities both in laboratory facilities and equipment and trained staff in molecular biology laboratory procedures. This article discusses a case of how science diplomacy and a relatively new law fostering public-private partnerships allowed a university to play a major role in public health response while generating knowledge to inform public policy decisions in an unprecedented manner in the country. Science diplomacy is discussed in the context of decolonization and the importance of the local gaze when creating academic partnerships in the context of global health emergencies.